2021
DOI: 10.3233/wor-213445
|View full text |Cite
|
Sign up to set email alerts
|

Job demands, work engagement and job turnover intentions among registered nurses: Explained by work-family private life inference

Abstract: BACKGROUND: The job demands on nurses have increased. Conflict between work life and family life may lead to stress and lower work engagement. Consequently, nurses may choose a different career path or leave the profession. OBJECTIVE: Examine the extent to which perceived job demands (interpersonal conflicts at work and workload), work engagement, work-family conflict and family-work conflict are associated with turnover intentions, and examine a possible moderating effect of work-family conflict on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
0
33
0
1
Order By: Relevance
“…A cross-sectional study in Sweden, in which 807 registered nurses participated, revealed that work-family conflict can be a strong predictor in nurses' turnover intention. Thus, managers should promote a positive work climate and a balance between nurses' work and family life in order to keep nurses in their profession [28].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Sweden, in which 807 registered nurses participated, revealed that work-family conflict can be a strong predictor in nurses' turnover intention. Thus, managers should promote a positive work climate and a balance between nurses' work and family life in order to keep nurses in their profession [28].…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare systems, the most common occupation for identifying, intercepting, and correcting life-threatening errors is nursing ( 7 ). The current study found that the turnover intention of unused nurses is affected by both internal and external components, such as person components counting gender, self-efficacy, work-family conflict, work environment, working hours, and so on ( 8 ). Currently, the turnover of nurses has been a major factor in nursing shortages, which hinders the development of nursing research and the sustainable development of practice ( 9 ).…”
Section: Introductionmentioning
confidence: 96%
“…In Italy and China, work engagement also has a significant negative impact on turnover intention [ 13 , 14 ]. Among emergency nurses, lack of work engagement is a significant predictor of turnover intention, job burnout and job dissatisfaction [ 15 , 16 ]. In a word, the role of work engagement is becoming more and more significant by achieving various positive results for organizations and individuals.…”
Section: Introductionmentioning
confidence: 99%